ASSESSING THE EFFICACY OF BAMBOO-REINFORCED CONCRETE FOR SUSTAINABLE LOW-COST HOUSING IN ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
Due to the increasing number of people in need of affordable housing in developing countries such as Anambra State, Nigeria, and the need to have sustainable construction, which was environmentally friendly, alternative materials that would be used to reinforce concrete have been sought. This paper assesses the effectiveness of bamboo-reinforced concrete as a promising alternative to low cost housing in terms of mechanical properties, durability, cost-effectiveness, and practical considerations to apply. By using mixed methods, the study was carried out at three locations in the State of Anambra: Awka, Onitsha and Nnewi which were chosen based on their varying soil types, population densities and housing demands. Locally, bamboo culms of the Bambusa vulgaris species were increased and added to the M20 grade concrete mixes by exposure to a 5% solution of borax to improve preservation. Tensile, compressive and bond tests were done using universal testing machines as comparative tests with steel-reinforced concrete as per the ASTM standards. Durability was tested by exposure to the tropical humid three months under the hot environment where degradation and intake of moisture were measured. The cost analysis entailed the sourcing of information in the local markets which led to an average of 35% reduction in the reinforcement cost in the case of bamboo. Tensile strengths of 160-195 Mpa, compressive strengths equivalent to steel after 28 days (somewhere 25-30 Mpa after 28 days on beams), and bond strengths increased with surface treatments were found. Depreciation tests indicated that there was under 4 per cent degradation, which affirmed that it is tough in humid conditions. The researchers used surveys of 150 respondents in low-income households in the study locations, of which 60 percent were aged between 25-45 years, were mainly urban migrants, and they experienced housing scarcity assessed at more than half a million units statewide. The findings highlight the potential of bamboo in saving up to 30-40 percent of construction costs and ensuring environmental sustainability but such issues as the fluctuation in the material properties imply standard requirements. The study will play a role in ensuring sustainable construction in tropical Africa which will promote policy instalment of bamboo in the national housing systems.